DETERMINANT OF INFERTILITY: INTERNAL AND EXTERNAL FACTORS IN A CROSS-SECTIONAL STUDY: DETERMINANT OF INFERTILITY: INTERNAL AND EXTERNAL FACTORS IN A CROSS-SECTIONAL STUDY - Fitriana, Shentya; Noviyanti, Catur Wida; Jehanara, Jehanara; Sari, Yulia; Sari, Gita Nirmala (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
Background: Infertility remains a major reproductive health problem globally, affecting 12–15% of Indonesian couples of reproductive ages. Both biological and lifestyle-related factors contribute to infertility, yet evidence on their relative influence in the Indonesian context is limited. Objectives: This study aimed to identify internal factors (tubal, uterine, ovulation, and sperm issues) and external factors (age, employment status, BMI, and smoking habits) influencing infertility. Methods: This analytical cross-sectional study was conducted at a government fertility clinic. A total of 343 infertile couples were included using a total sampling approach. Secondary data were extracted from medical records using a structured checklist encompassing socio-demographic, lifestyle, and clinical reproductive variables. The dependent variable was infertility type. Independent variables included age, occupation, BMI, smoking, and reproductive organ factors. Bivariate analysis was performed using Chi-square tests, and variables with p < 0.25 were entered into multiple logistic regression to determine the most influential predictors of infertility. Results: Wife’s age (p = 0.001), husband’s age (p = 0.014), ovulation disorders (p < 0.001), and sperm abnormalities (p < 0.001) were significantly associated with infertility. Multivariate analysis identified ovulation disorders (OR = 2.34; 95% CI: 1.35–4.03) and sperm abnormalities (OR = 2.52; 95% CI: 1.45–4.37) as the dominant predictors. Conclusion: Infertility among Indonesian couples is primarily influenced by ovulation and sperm abnormalities, underscoring the need for early reproductive health screening and lifestyle-based prevention strategies.